HLA-B gene somatic insertion/deletion mutations in patients with acute myelogenous leukaemia - Königova, Nikola; Skoumalova, Ivana; Onderkova, Jana; Ambruzova, Zuzana; Szotkowski, Tomas; Koristek, Zdenek; Maluskova, Alena; Raida, Ludek; Mrazek, Frantisek (International journal of immunogenetics, 2018)
Loss of heterozygosity is considered to be the most common type of tumour-specific somatic mutation of the human leucocyte antigens (HLA) genes in patients with haematological malignancies. Nevertheless, subtle DNA sequence changes, namely short insertions/deletions, may also abolish the expression of HLA molecules and interfere with routine HLA typing. Two male patients with acute myelogenous leukaemia (AML) were indicated for the search of a suitable donor for allogeneic haematopoietic stem cell transplantation (aHSCT). The patients and their relatives were initially HLA typed by serological and DNA techniques at a low-resolution level. The HLA high-resolution (HR) type was obtained by means of sequencing-based typing (SBT). In both cases, anomalous frameshifts in the sequence were observed in the HLA-B gene, namely in exon 3 (Case 1, heterozygous deletion of two bases) and exon 4 (Case 2, heterozygous insertion of two bases). In the second case, the insertion variant was associated with a loss of HLA-B8 expression. To reveal whether these sequence patterns may be caused by somatic mutations in the malignant cells, blood sample in remission (Case 1) and buccal swab sample (Case 2) were collected from the patients. In an important manner, the SBT in these germline samples revealed common HLA-B*07:02,*15:01 (Case 1) and HLA-B*08:01,*35:02 (Case 2) types with no evidence for the sequence alteration observed in the initial samples. In conclusion, the insertion/deletion sequence variants of the HLA-B gene in two patients were limited to the initial blood samples with a substantial proportion of AML cells and thus may be attributed to the somatic mutation in the malignant cells. HLA somatic mutations should be taken into account in patients with haematological malignancies to prevent HLA mistyping and inappropriate selection of an aHSCT donor.
Keywords: HLA-B8 antigen; immune response; HLA; allograft/allogeneic transplantation; lidé; mutace INDEL; HLA-B8 Antigen; INDEL Mutation; cancer - leukaemia/haematologic; HLA-B7 Antigen; Male; akutní myeloidní leukemie; nádorové proteiny; Neoplasm Proteins; HLA-B7 antigen; lidé středního věku; mužské pohlaví; Middle Aged; Leukemia, Myeloid, Acute; Humans